2019
DOI: 10.1007/s11934-019-0877-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Endoscopic Surgery (SBES) for Bilateral Urolithiasis: the Future? Evidence from a Systematic Review

Abstract: Purpose of Review Urolithiasis is a disease of prevalence across the world and up to a quarter of patients present with multiple stones. Most procedures carried out in this scenario are staged; however, there is a growing body of evidence to suggest bilateral simultaneous (BS) procedures are safe. We performed a systematic review to investigate and evaluate the evidence for these procedures. Recent Findings A systematic review was conducted according to Cochrane and PRISMA checklist for all English-language ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Three systematic reviews highlighted the lack of highquality evidence on BSS RIRS in the management of urolithiasis. 6,7,10 Previous retrospective series reported that SFR ranged from 42.0% to 92.8%. [11][12][13][14][15][16] This wide range reflects the different image modalities used to evaluate this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews highlighted the lack of highquality evidence on BSS RIRS in the management of urolithiasis. 6,7,10 Previous retrospective series reported that SFR ranged from 42.0% to 92.8%. [11][12][13][14][15][16] This wide range reflects the different image modalities used to evaluate this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…With further digitisation of technology, reduction in scope size and improved laser fragmentation, it seems that the uptake of URS is going to increase for paediatric patients. Similarly, its role in complex patient groups or bilateral urolithiasis is likely to continue to evolve [35,36]. Recent evidence shows that outcomes for bilateral URS procedures are at least equivalent to staged procedures, minimising cost and hospital stay [36].…”
Section: Role Of Ureteroscopy (Urs)mentioning
confidence: 99%
“…Similarly, its role in complex patient groups or bilateral urolithiasis is likely to continue to evolve [35,36]. Recent evidence shows that outcomes for bilateral URS procedures are at least equivalent to staged procedures, minimising cost and hospital stay [36]. Perhaps, the paediatric urolithiasis guidelines need to address the role of access sheath, and ureteroscopy for large stones and lower pole stones.…”
Section: Role Of Ureteroscopy (Urs)mentioning
confidence: 99%
“…For decades, simultaneous surgical treatment of bilateral renal stones has been considered a risk factor for acute renal failure and a higher incidence of complications. Notwithstanding these popular statements, some studies have shown that bilateral endoscopic interventions on the kidneys were safe not only with staged treatment from different angles [43,44] but also with a simultaneous approach [45,46]. In a series of works by R. Giusti et al on simultaneous bilateral flexible ureteronephrolithotripsy, they have described that this method was effective and safe, provided proper selection and preoperative preparation of patients.…”
Section: Resultsmentioning
confidence: 99%